Primary neonatal ileoileal intussusception - Ahmed Hassan; Mostafa Zain; Yasmine Ghazaly (Journal of Pediatric Surgery Case Reports, 2019)
Intussusception is a very rare cause of intestinal obstruction in neonatal age and early infancy. We present a case of 26-day- female who presented with abdominal distension, bilious vomiting and bleeding per rectum. The initial diagnosis was intestinal obstruction due to volvulus or malrotation On exploratory laparotomy, it turned out to be a case of ileo-ileal intussusception without any leading point. This site of intussusception (ileo-ileal) and without any leading point (idiopathic or primary intussusception) among neonate is of exceedingly rare occurrence and very few such cases have been reported. In this article, the published work about clinical features and management on intussusceptions in neonatal period and early infancy has been reviewed. The authors intend to highlight the difficulty in distinguishing the intussusception. Subtle clinical and radiological features which can help the condition to be emphasized. This can avoid the delay in diagnosis and management which can prove critical. High index of suspicion with timely intervention is the key for optimizing outcome. A diagnosis of intussusception should always be considered in any neonate or infant with suspected intestinal obstruction. Keywords: Ileo-ileal intussusception, Small bowel intussusception, Resection anastomosis